Los Angeles Latino Museum Finding Guide - Taylor, Evelyn::::::
The Latino Museum Collection Box Listing acts as a finding guide to the majority of contents of the collection; it does not list all contents, as not all items have been processed or are confidential. It provides detailed information of the content, such as titles to publications, authors, dates of publications, and helpful notes for identification.